Potential inhibitory effect of carbon dioxide on the spoilage behaviors of Pseudomonas fragi in high-oxygen packaged beef during refrigerated storage. (June 2023) - Yang, Jun; Liang, Rongrong; Mao, Yanwei; Dong, Pengcheng; Zhu, Lixian; Luo, Xin; Zhang, Yimin; Yang, Xiaoyin
Abstract: Pseudomonas fragi is a dominant meat spoilage organism under high-oxygen modified atmosphere packaging (HiOx-MAP). This work investigated the effects of CO2 on P. fragi growth and the related spoilage phenomena of HiOx-MAP beef. Minced beef incubated with P. fragi T1, a strain owning the strongest spoilage potential among isolates, was stored under CO2 -enriched HiOx-MAP (TMAP; 50% O2 /40% CO2 /10% N2 ) or non-CO2 HiOx-MAP (CMAP; 50% O2 /50% N2 ) at 4 °C for 14 days. Compared to CMAP, TMAP maintained sufficient O2 levels to endow beef with higher a * values and meat color stability due to lower P. fragi counts from day 1 ( P < 0.05). TMAP samples also showed lower ( P < 0.05) lipase activity and protease activity within 14-days and 6-days than CMAP samples respectively. TMAP delayed the significantly increased pH and total volatile basic nitrogen contents occurred in CMAP beef during storage. Despite TMAP markedly promoted the lipid oxidation associated with higher concentrations of hexanal and 2, 3-octanedione than CMAP ( P < 0.05), TMAP beef retained an acceptable organoleptic odor due to a CO2 -inhibition on the microbial-induced 2, 3-butanedione and ethyl 2-butenoate formation. This study provided a comprehensive insight into the antibacterial mechanism of CO2 on P. fragi in HiOx-MAP beef. Graphical abstract: Image 1 Highlights: CO2 inhibited P. fragi growth and retained satisfactory sensory acceptability. P. fragi extracellular lipase and protease activity were influenced by CO2 . CO2 reduced the 2, 3-butanedione and ethyl 2-butenoate levels produced by P. fragi. HiOx-MAP enriched in CO2 promoted lipid oxidation associated with abundant VOCs.